DYEING AT HOME FROM KITCHEN WASTE - TEA AND COFFEE RESIDUE - R, Preetha; Rani, Nancy Angeline (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Food and Textile industries are considered to be the most vital industries for human survival. The food industry generates an enormous amount of waste which is used as animal feed or undergoes composting or just go as landfills. Some of these organic wastes contains colouring pigments which can be effectively used to colour textiles. Hence there is a possibility to bridge the gap utilizing the waste from food industry to colour textile materials. Chemical dyes are easier to use and produce bright shades but on the other hand it causes pollution to the environment. Natural dyes from plant sources are required in large amounts which may cause depletion of natural resources. Considering these factors, the waste material from food industry, which is available at little, or no cost can be effectively used to colour textiles, this would make natural dyeing affordable and bring about sustainability in textile dyeing process. This kind of sustainable approach protects the environment by utilizing the waste produced by one industry and creating a value-added item for another industry. This study was carried out considering the sustainability aspect which is mutually beneficial to food and textile industries. Natural dyes can be found in the kitchen or in one’s garden can produce beautiful hues. A simple dyeing process can be used to colour the fabric at home utilising available resources in the home kitchen. Decoction waste after extracting two widely used beverages - tea dust and filter coffee dust which are part of everyday kitchen waste were used for the study. Instead of these wastes going directly as landfills, dye was extracted prior to its disposal. Cotton fabric, mordanted with Alum, was dyed with the extracted dye. These dyed fabrics showed good to excellent colour fastness to perspiration, rubbing, washing, and pressing. Since these dyes are natural in origin, they are safe and eco-friendly. This study proves that throw-away kitchen waste can be utilized to extract dyes that can be used to create value-added products.